Upper bound of mean-square deviation of discrete linear consensus system - Quan-sheng DOU; Yu-rong LI; Ping JIANG (Tongxin xuebao)
The consistency problem is the basis of cooperative control of multi-agents,and has wide application background.The previous research has given the sufficient condition for the linear consistency protocol to realize mean-square consistency problem .Based on graph theory and random analysis,the noise-deviation upper bound of linear discrete mean-square consistency problem was strictly proved further,at the same time,four different network were used as examples to explain the theoretical results.The conclusion provides theoretical basis for the noise evaluation and control of the linear discrete consistency system.